2014
DOI: 10.1371/journal.pone.0115466
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence for the Involvement of Loosely Bound Plastosemiquinones in Superoxide Anion Radical Production in Photosystem II

Abstract: Recent evidence has indicated the presence of novel plastoquinone-binding sites, QC and QD, in photosystem II (PSII). Here, we investigated the potential involvement of loosely bound plastosemiquinones in superoxide anion radical (O2 •−) formation in spinach PSII membranes using electron paramagnetic resonance (EPR) spin-trapping spectroscopy. Illumination of PSII membranes in the presence of the spin trap EMPO (5-(ethoxycarbonyl)-5-methyl-1-pyrroline N-oxide) resulted in the formation of O2 •−, which was moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 47 publications
(80 reference statements)
1
12
0
Order By: Relevance
“…To explain O 2 reduction via an apparently thermodynamically unlikely reaction, it has been suggested that the A possible alternative solution is that cyt b559 mediates the formation of semiquinones at Q D and Q C sites. Experimental evidence of the reduction in O 2 by a loosely bound plastosemiquinone anion radical (PQ •− ) at the Q C site was provided by Yadav et al [250]. The authors showed that PQ •− can be formed by a one electron reduction in PQ at the Q B site and one electron oxidation of PQH 2 by cyt b559 at the Q C site.…”
Section: Oxygen Reduction In Petcmentioning
confidence: 99%
“…To explain O 2 reduction via an apparently thermodynamically unlikely reaction, it has been suggested that the A possible alternative solution is that cyt b559 mediates the formation of semiquinones at Q D and Q C sites. Experimental evidence of the reduction in O 2 by a loosely bound plastosemiquinone anion radical (PQ •− ) at the Q C site was provided by Yadav et al [250]. The authors showed that PQ •− can be formed by a one electron reduction in PQ at the Q B site and one electron oxidation of PQH 2 by cyt b559 at the Q C site.…”
Section: Oxygen Reduction In Petcmentioning
confidence: 99%
“…Pheophytin (Pheo D1 •– ), tightly bound plastosemiquinone (Q A •– ), loosely bound plastosemiquinones (Q B •– or Q C •– ), free PQ (PQ •– ), and ferrous iron of LP form of cyt b 559 were proposed to serve as electron donors to O 2 (Ananyev et al, 1994; Cleland and Grace, 1999; Pospíšil et al, 2004, 2006; Yadav et al, 2014). As Pheo D1 •– has highly negative redox potential, the reduction of O 2 by Pheo D1 •– is thermodynamically feasible; however, its short lifetime makes the diffusion limited reduction of O 2 less reasonable.…”
Section: High Lightmentioning
confidence: 99%
“…The detection of O 2 •– in isolated thylakoids by a voltammetric method showed O 2 •– production by the tightly bound plastosemiquinone Q A •– (Cleland and Grace, 1999). Experimental evidence has been recently provided on the reduction of O 2 by the loosely bound plastosemiquinones (Yadav et al, 2014). The authors demonstrated that plastosemiquinone is formed by the one-electron reduction of plastoquinone at the Q B site and the one-electron oxidation of plastoquinol by cyt b 559 at the Q C site.…”
Section: High Lightmentioning
confidence: 99%
“…Formation of O results from non-enzymatic and enzymatic one-electron reductions of molecular oxygen. Pheophytin (Pheo •− ) (Ananyev et al, 1994 ; Pospíšil et al, 2004 ), tightly bound plastosemiquinone (Q ), (Cleland and Grace, 1999 ; Pospíšil et al, 2004 ), loosely bound plastosemiquinone (Q ), (Zhang et al, 2003 ; Yadav et al, 2014 ), and free plastosemiquinone (PQ •− ) (Mubarakshina and Ivanov, 2010 ) maintains non-enzymatic reduction of molecular oxygen to O . Heme iron of low-potential (LP) form of cyt b 559 reduces molecular oxygen to O in the enzymatic reaction pathway (Pospíšil et al, 2006 ; Pospišil, 2011 ).…”
Section: Introductionmentioning
confidence: 99%